Computer simulation studies on the effect overlap ratio for savonius type vertical axis marine current turbine - Yaakob, Omar (Materials and Energy Research Center, 2010)
The Ocean has provided a new avenue in the quest for renewable energy. One potential source of energy is marine current, which is harnessed using either vertical or horizontal axis turbines. This paper describes a particular type of vertical axis turbine which is suitable for low current velocity applications. The simulation of Savonius-type turbine, which hitherto has never been proposed for marine current energy application, is presented in this paper. A 3D computational model was built and analyzed using a Computational Fluid Dynamic analysis using proprietary software. The overlap ratio is identified as one of the important factors in Savonius turbine performance. This paper provides results of the investigation for a range of overlap ratios between 0.1 and 0.6 and it was found that the maximum torque can be obtained at overlap ratio of 0.21.